Spontaneous cervical and mediastinal hematoma due to rupture of inferior thyroid artery - Takayuki Yamada, MD, PhD; Satoru Yanagaki, MD, PhD; Nozomi Satani, MD, PhD; Yuriko Kagaya, MD; Tomoni Sato, MD, PhD; Tomonori Matsuura, MD, PhD; Teruyuki Sato, MD, PhD; Naoya Noguchi, MD, PhD; Nobuo Ohta, MD, PhD (Radiology Case Reports)
A 62-year-old man was referred to our hospital presenting with a sore throat, dyspnea, and cervical swelling. Initial precontrast CT scans revealed a cervical and mediastinal hematoma, along with a hemothorax. Further dynamic contrast-enhanced CT scans indicated contrast media extravasation dorsal to the right thyroid gland lobe, suggesting a rupture of the right inferior thyroid artery or a parathyroid adenoma. Following endotracheal intubation, angiography confirmed extravasation from the right inferior thyroid artery. Transarterial embolization (TAE) was successfully performed using a gelatin sponge. The cervical and mediastinal hematoma were surgically excised, and the right inferior parathyroid gland was simultaneously resected. Pathological examination revealed no neoplastic components.